Neuronal deficiency of p38α‐MAPK ameliorates symptoms and pathology of APP or Tau‐transgenic Alzheimer's mouse models. Issue 7 (31st May 2020) - Schnöder, Laura; Gasparoni, Gilles; Nordström, Karl; Schottek, Andrea; Tomic, Inge; Christmann, Anne; Schäfer, Karl H.; Menger, Michael D.; Walter, Jörn; Fassbender, Klaus; Liu, Yang
Abstract: Alzheimer's disease (AD) is the leading cause of dementia with very limited therapeutic options. Amyloid β (Aβ) and phosphorylated Tau (p‐Tau) are key pathogenic molecules in AD. P38α‐MAPK is specifically activated in AD lesion sites. However, its effects on AD pathogenesis, especially on p‐Tau‐associated brain pathology, and the underlying molecular mechanisms remain unclear. We mated human APP‐transgenic mice and human P301S Tau‐transgenic mice with mapk14 ‐floxed and neuron‐specific Cre‐knock‐in mice. We observed that deletion of p38α‐MAPK specifically in neurons improves the cognitive function of both 9‐month‐old APP and Tau‐transgenic AD mice, which is associated with decreased Aβ and p‐Tau load in the brain. We further used next‐generation sequencing to analyze the gene transcription in brains of p38α‐MAPK deficient and wild‐type APP‐transgenic mice, which indicated that deletion of p38α‐MAPK regulates the transcription of calcium homeostasis‐related genes, especially downregulates the expression of grin2a, a gene encoding NMDAR subunit NR2A. Cell culture experiments further verified that deletion of p38α‐MAPK inhibits NMDA‐triggered calcium influx and neuronal apoptosis. Our systemic studies of AD pathogenic mechanisms using both APP‐ and Tau‐transgenic mice suggested that deletion of neuronal p38α‐MAPK attenuates AD‐associated brain pathology and protects neurons in AD pathogenesis. This study supports p38α‐MAPK as a novel target for AD therapy.